2020
DOI: 10.1111/gcb.14984
|View full text |Cite
|
Sign up to set email alerts
|

Lower‐than‐expected CH4 emissions from rice paddies with rising CO2 concentrations

Abstract: Elevated atmospheric CO2 (eCO2) generally increases carbon input in rice paddy soils and stimulates the growth of methane‐producing microorganisms. Therefore, eCO2 is widely expected to increase methane (CH4) emissions from rice agriculture, a major source of anthropogenic CH4. Agricultural practices strongly affect CH4 emissions from rice paddies as well, but whether these practices modulate effects of eCO2 is unclear. Here we show, by combining a series of experiments and meta‐analyses, that whereas eCO2 str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…We found that straw return increased SOC sequestration for paddy rice by 3.0 Mg CO 2 eq ha −1 year −1 (Figure 1i). However, straw decomposition can provide substantial methanogenic substrates for CH 4 production (Ma et al, 2008; Qian et al, 2020). We found that the enhanced SOC sequestration was completely offset by straw‐induced CH 4 emissions (Figure S3; Figure 1c), with relatively small changes in N 2 O emissions (Figure S3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that straw return increased SOC sequestration for paddy rice by 3.0 Mg CO 2 eq ha −1 year −1 (Figure 1i). However, straw decomposition can provide substantial methanogenic substrates for CH 4 production (Ma et al, 2008; Qian et al, 2020). We found that the enhanced SOC sequestration was completely offset by straw‐induced CH 4 emissions (Figure S3; Figure 1c), with relatively small changes in N 2 O emissions (Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic N fertilizer replacement promotes SOC accumulation by directly adding exogenous organic materials, and increasing the inputs of root and root exudate to soils through stimulating crop growth (Majumder et al, 2008; Pan et al, 2009; Xia et al, 2014; Yan & Gong, 2010). However, the decomposition of organic addition enhanced methanogens activities for CH 4 production (Ma et al, 2008; Qian et al, 2020). All proportions of synthetic N fertilizer replacements significantly stimulated CH 4 emissions, with the largest at 100% replacement ( p < .05, Figure S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional prominent example of the potential of microbial trait-based approaches regarding greenhouse gas emissions in agroecosystems concerns the emission of the potent greenhouse gas methane from rice agriculture, contributing approximately 11% to the total anthropogenic methane emissions (Saunois et al, 2020). Combined with the projected accelerating effects of increasing temperature and CO2 on rice associated GHG emissions (Bodelier and Steenbergh, 2014;Qian et al, 2020), the quest for high productivity rice with low climate impact is a model example for a plant-microbe trait-based approach with the goal to mitigate climate change (Paustian et al, 2016). The rice microbiome has been increasingly investigated in the quest for climate-smart and sustainable rice, searching for microbes with beneficial traits for growth and development of various parts of the rice plants (Edwards et al, 2015;Kim and Lee, 2020).…”
Section: Microbial Traits Related To Greenhouse Gas Emissionsmentioning
confidence: 99%
“…The soil physical and biogeochemical properties are particularly dynamic in paddy soils due to long-term, managed oxidation and reduction cycles. Previous studies have mainly focused on organic carbon (C) dynamics (Wei et al, 2018), greenhouse gas emissions (Zhu et al, 2018;Liu G et al, 2019;Qian et al, 2020), and soil microbial properties (Watanabe et al, 2020). In addition, puddling of paddy soils strongly influences soil structure characteristics (Zhou et al, 2016) with structure destruction reducing infiltration, which can increase surface runoff and loss of NNPs with associated contaminants (Zhang and Gong, 2003).…”
Section: Introductionmentioning
confidence: 99%